The role of MMP-2 and MMP-9 in the metastasis and development of hypopharyngeal carcinoma - Song,Zhe (2021)
Abstract Introduction: The role of matrix metalloproteinase-2 and 9 in the metastasis and development of hypopharyngeal carcinoma has not been clarified. Objectives: To observe the relationship between matrix metalloproteinase-2, matrix metalloproteinase-9 and the metastasis, development of hypopharyngeal carcinoma. Methods: This study included 42 hypopharyngeal cancer patients. The mRNA and protein expression levels of matrix metalloproteinase-2 and 9 in hypopharyngeal carcinoma and paracancerous tissues were detected by reverse transcription-polymerase chain reaction and Western blot. Results: Reverse transcription-polymerase chain reaction detection showed that the mRNA of matrix metalloproteinase-2 and 9 was expressed in both cancer and pericarcinoma tissues, but was almost not expressed in polypoid control tissues. The expression intensity in the cancer tissue was significantly higher than that in the pericarcinoma tissue (matrix metalloproteinase-2: t = 2.529, p = 0.015; matrix metalloproteinase-9: t = 4.781, p <0.001). The mRNA expression in the cancer tissue was enhanced with the increase of the tumor clinical stage (matrix metalloproteinase-2: F = 4.003, p = 0.026; matrix metalloproteinase-9: F = 5.501, p = 0.008). Its expression intensity was associated with the metastasis of lymph nodes (N staging) and increased with the degree of lymphatic metastasis (matrix metalloproteinases-2: F = 8.965, p = 0.005; matrix metalloproteinase-9: F = 5.420, p = 0.025). There was no significant change in T staging of tumor. With the increase of tumor pathological stage, the mRNA expression of matrix metalloproteinase-2 and 9 was strengthened (matrix metalloproteinase-2: F = 3.884, p = 0.029; matrix metalloproteinase-9: F = 3.783, p = 0.032). The protein expression level of matrix metalloproteinase-2 and 9 was the same as that of mRNA. Conclusion: The expression of matrix metalloproteinase-2 and 9 in hypopharyngeal carcinoma was significantly higher than that in pericarcinoma tissue, and it was enhanced with the increase of clinical stage. The expression level was related to lymph node metastasis and tumor pathological stage. Thus, matrix metalloproteinase-2 and 9 may be involved in the occurrence, development, invasion and metastasis of hypopharyngeal carcinoma through a variety of mechanisms.